En el marco de inclusión: prácticas en una escuela de referencia en Colombia - Yudi Esmeralda Pardo Murcia (2021)
Public policies in Colombia in recent years have stipulated reforms in the educational system; reaffirming the right to education of all children and adolescents in Colombia and calling for the school as a space that welcomes diversity within the framework of inclusive education. However, it is recognized that the admission of all students —including those populations that have been excluded and violated, among them, people with disabilities— does not guarantee the existence of an inclusive education. In this sense, this paper focuses on the role of the educators with the aim of analyzing and understanding the elements of teachers' pedagogical practices that enable or create barriers in the inclusion of students with disabilities. For this purpose, this study develops a theoretical framework that covers different positions regarding the inclusive pedagogical practices of teachers with students with disabilities, providing elements that allow understanding the reality within a school in Bogota that is a reference for its trajectory in the path towards inclusive education, even before it was stipulated in the public policy of Colombia. This research has been developed through interviews and participant observation, achieving an approach to the reality in the educational institution and to the pedagogical practices of teachers, which has allowed defining categories that through their analysis perceived different practices evidencing possible paths towards an inclusive education, as well as those that are naturalized as inclusive, but that fall back on exclusionary practices.